Narrating the city : histories, space, and the everyday - Fischer-Nebmaier, Wladimir; Berg, Matthew Paul, 1961-; Christou, Anastasia (Space and place ;, 2015)
"In recent decades, the insight that narration shapes our perception of reality has inspired and influenced the most innovative historical accounts. Focusing on new research, this volume explores the history of non-elite populations in cities from Caracas to Vienna, and Paris to Belgrade. Narration is central to the theme of each contribution, whether as a means of description, a methodological approach, or basic story telling. This book brings together research that both asks classical socio-historical questions and takes narration seriously, engaging with novels, films, local history accounts, petitions to municipal authorities, and interviews with alternative cinema activists"--Provided by publisher.